Six Sessions of Low-volume High-intensity Interval Exercise Improves Resting Fat Oxidation - Atakan, Muhammed Mustafa; Koşar, Şükran Nazan; Turnagöl, Hüseyin Hüsrev (International Journal of Sports Medicine, 2022)
It remains unclear whether a practical model of low-volume high-intensity interval exercise improves resting fat oxidation (FatOx) that is associated with metabolic health. We aimed to determine the effects of a short-term practical model of high-intensity interval training (HIIT) on resting FatOx in young, healthy males. Thirty healthy males were randomly assigned to either single (HIITsingle; n=13) or double HIIT (HIITdouble; n=17) group. The HIITsingle group trained once a day, 3 days/week for 2 weeks, whilst the HIITdouble group performed 6 sessions of high-intensity exercise over 5 days by exercising twice a day every second day. Both groups completed 6 high-intensity exercise sessions consisting of 10×60 s of cycling at peak power output, interspersed by 75 s cycling at 60 W. With 1% false discovery rate (FDR) significance threshold, resting respiratory exchange ratio similarly decreased in HIITsingle (pre=0.83±0.03 vs post=0.80±0.03) and HIITdouble group (pre=0.82±0.04 vs post=0.80±0.02) [(p=0.001; partial eta squared (η)=0.310, FDR-adjusted p value=0.005)]. Resting FatOx increased similarly in HIITsingle (pre=1.07±0.39 mg·kg-1 fat free mass (FFM)·min-1 vs post=1.44±0.36 mg·kg-1 FFM·min-1) and HIITdouble group (pre=1.35±0.45 mg·kg-1 FFM·min-1 vs post=1.52±0.29 mg·kg-1 FFM·min-1) [(p<0.001; η=0.411, FDR-adjusted p value=0.005)]. Our results demonstrate that only six sessions of a practical model of low-volume high-intensity exercise improves resting FatOx in young, healthy males.
Keywords: exercise; metabolism; lipid oxidation; HIIT; body composition